Chronic Brucella infection of the supra-patellar bursa with sinus formation. Issue 8 (August 1994) - McDermott, M; O'Connell, B; Mulvihill, T E; Sweeney, E C
Abstract : A case of supra-patellar bursitis with the formation of discharging sinus is described. B abortus was isolated from resected bursal tissue. While osteoarticular complications of brucellosis are common and a number of different clinical syndromes are now recognised, disease of the bursae is rare and as far as is known sinus formation has not been described before in this setting.